(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Organizations always strive for superior performances for which they create numerous plans and strategies. Performance management is one such important process with the help of it the organizations can create a work system environment which will be able to generate optimal utilization of resources and desired performance. Performance of employees has always been a factor of critical interest and worry. Superseding the performance appraisal system performance management concept has come in vogue.This research article is a review of various facets of performance management and discusses the benefits of having a performance management system in one’s organization.